Obtaining the thermal resistance of air enclosed at the interface of multilayer fabrics by simulation. Issue 15 (August 2019) - Shen, Hua; Tu, Lexi; Yan, Xiaofei; Sukigara, Sachiko
An air layer enclosed at the interface was largely responsible for the insulation results of multilayer fabrics obtained from experiments. In this study, a three-dimensional finite element method model, in which the air layer enclosed at the interface of multilayer fabrics was ignored, was developed to calculate the fabric thermal resistance, and the result obtained from the fabric model was independent of the air. A Thermolab II Tester KES-F7 was also used to measure the thermal resistance of fabrics, and the experimental results were influenced by the air layer. By comparing the simulation and experimental result, the air layer thermal resistance was determined, and then an estimating equation, which can be used to estimate the fabric and air layer thermal resistance for multilayer fabrics, was proposed. The results suggested that the surface roughness of fabrics was strongly related to the air layer thermal resistance, with a linear relationship between them. Moreover, for multiple layers stacked by different fabrics, the air layer thermal resistance at the interface was mainly decided by the fabric with the rougher surface. An estimating equation was also developed to predict the thermal resistance of multilayer fabrics and good correlation between predicted and experimental values was observed.